An improved approximation for the determination of the average RCS of cylinders and flat plates and for the directivity of broadside arrays. - Mahony, John D.
An integral commonly occurring in analyses associated with RCS calculations and directivity calculations for uniform arrays is re-examined. Typically, such integrals are evaluated either numerically (a tedious business) or approximately (using asymptotic methods for large arguments). It is shown here that by incorporating only the next higher-order term in the usual asymptotic development for such integrals, it is possible to secure a significant improvement in integral-estimation accuracy, at very little increase in computational effort.
Keywords: Radar cross sections; Antenna arrays; Numerical analysis; Cylinders; Flat plates